Implementasi Program Wisuda Tahfidz untuk Meningkatkan Motivasi Menghafal Al-Qur’an Santri di Rumah Tahfidz Desa Ciranjeng - Agni Alfia Zahra; Desi Rahmawati; Deis Sintiya; Faiz Azhari; Leni Latopah; Nazda Maryamul Ulfa; Nia Namira Anjani; Yuni Nur Anggraeni (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The low motivation of students in memorizing the Qur’an at the Tahfidz House in Ciranjeng Village has become a problem that encourages the implementation of the tahfidz graduation program as an innovation in learning development. This study aims to analyze the implementation of the tahfidz graduation program and its effect on increasing students’ motivation in memorizing the Qur’an. The problems examined include the implementation process of the program, changes in students’ motivation before and after the program, and the effectiveness of the program in supporting memorization achievement. This study uses a descriptive method with a qualitative approach and an action research design. Data collection techniques include observation, interviews, and documentation, while data analysis is carried out descriptively through data reduction, data presentation, and conclusion drawing. The results show that the tahfidz graduation program is able to significantly increase students’ motivation, as indicated by improved discipline, consistency in memorization, and increased memorization achievements. In addition, parental involvement and appreciation through the graduation program have a positive psychological impact on students, encouraging them to be more enthusiastic in memorizing the Qur’an.